Excluding the species Monoon fragrans (Annonaceae) from the flora of China - Xue, Bine; Nurmawati, Subekti; Xu, Yuan; Li, Yong-Quan (Phytotaxa, 2021)
The distribution of Monoon fragrans (≡ Polyalthia fragrans) in China was first recorded in Flora of China in 2011. According to detailed specimen investigation, we found that the Chinese specimens identified previously as Polyalthia fragrans actually represent Monoon simiarum (≡ Polyalthia simiarum). Extensive field investigation also fails to discover the distribution of Monoon fragrans in China. Thus, results from field investigation and specimen examination suggest that M. fragrans is an endemic species to India and its distribution in China should be excluded. Morphologically, M. fragrans can be distinguished from M. simiarum by its tomentose peduncles, narrowly linear petals which are puberulous on both sides, ovoid puberulous monocarp with puberulous stipes and brittle pericarp, as well as the orbicular-ovoid seed.